Conversion Factors - Frederick M. Fishel; Jason A. Ferrell; Gregory E. MacDonald (EDIS, 2007)
Revised! SS-AGR-27, a 3-page fact sheet by F.M. Fishel, J.A. Ferrell, and G. E. MacDonald, provides conversion factors for mass, area, velocity, pressure, temperature, length, liquid, and commodity weights, plus a list of abbreviations. Published by the UF Department of Agronomy, May 2007.